Pengaruh Motivasi dan Kompensasi terhadap Kinerja Karyawan pada PT. Indoguna Utama - Muhammad Rizky Ramadhan; Natal Indra (Jurnal Bintang Manajemen, 2024)
This research aims to find out how much influence motivation and compensation have on employee performance at PT Indoguna Utama. The research method used is a quantitative approach, with a population of 65 employees and a sample of 40 people. The sampling technique uses the Slovin formula. Data collection used a questionnaire in multiple linear regression analysis units and hypothesis testing. Data processing uses SPSS 24 software for instrument testing, multiple linear regression analysis, and hypothesis testing. The research results show that both partially and simultaneously motivation and the work environment have a positive effect on the performance of PT Indoguna Utama.